Tuberculosis and Single Nucleotide Polymorphisms in the SP-A Gene - Urooj Subhan; Ezza Binte Tariq; Farah Deeba; Sidra Younis (Life and Science)
Tuberculosis (TB), is a primary global health concern, caused by Mycobacterium tuberculosis (MTB). Pakistan is ranked 5th among highly prevalent TB countries. Susceptibility to TB is affected by several biological variables, including age, gender, host genetics, and host immunity. Among these, host genetics is a key factor because it not only affects the probability of TB susceptibility but also aggravates its clinical manifestations. Understanding the contribution of host genetics in the protection, proneness, and progression of TB is of paramount importance. The host's innate immune system offers protective genes that promote uptake and clearance of MTB and detrimental genes that promote survival and progression of MTB. Surfactant protein A (SP-A) is an essential constituent of innate immunity involved in the host defense against various pathogens, particularly MTB. SP-A acts as a bridge between MTB and macrophages as it interacts with the glycoprotein located on the surface of MTB and mannose receptors present on the surface of alveolar macrophages, consequently enhancing the engulfment of MTB. This gene is also important in LTBI as it is involved in the progression of LTBI to active TB. A variety of single nucleotide polymorphisms (SNPs) are in the exonic and intronic regions of SP-A gene that may affect its expression hence MTB uptake into macrophages. SP-A polymorphisms have been investigated in various diseases but not specifically for TB and LTBI in the Pakistani population. This review is aimed at summarizing existing literature on SP-A gene polymorphisms and their impact on SP-A gene expression in pulmonary as well as extrapulmonary disorders. This study will assist in choosing candidate polymorphisms that can be further investigated in TB and LTBI patients from the Pakistani population. Total of 17 Studies were identified reporting 79 SPA gene polymorphisms including rs1059047, rs1136450, rs1059049, rs1059054, rs4253527, rs1136452, rs1914663, rs1059225, rs17880809, rs1965708, rs17886395, rs1059046, rs17879335, rs17881720 in pulmonary and extra pulmonary disorders. Conclusion: We conclude that rs1059047 is most commonly studied SNP that has a significant effect on expression of SP-A gene and is an appropriate candidate to be investigated in LTBI and active TB.